Increasing Knowledge And Skills Of Pregnant Mothers In The Effort To Prevent Stunting In The Work Area Of Pekanheran Health Center, Indragiri Hulu Regency - Elmukhsinur Elmukhsinur (PITIMAS: Journal of Community Engagement in Health, 2022)
Stunting is a major nutritional problem that faced by Indonesia. Stunting can cause developmental disorders in children, especially in children under two years. Malnutrition factor in pregnant women and toddlers is the main factor that causes stunting. One of the causes of malnutrition in pregnant women is inadequate knowledge of mothers about a balanced nutrition for pregnant women. This community service aims to increase the knowledge and skills of pregnant women in stunting prevention efforts. The method of this community service activity is counseling about stunting, exclusive breastfeeding, balanced nutrition for pregnant women as well as simulations and practices of making a balanced nutrition menus for pregnant women and breast care. Data on knowledge and skills results are statistically tested with the Paired sample T-test. The results of statistical tests showed an increase in knowledge of pregnant women about stunting, exclusive breastfeeding and balanced nutrition after being given counseling. As well as the skills of pregnant women in making and compiling a balanced nutrition menu and breast care. There was an increase after the simulation and practice of making and compiling a balanced nutrition menu for pregnant women and breast care.